Medidas protetivas de urgência e o poder judiciário maranhense: avaliação da eficácia da prestação jurisdicional estatal nos julgamentos de medidas protetivas de urgência através da análise de seus recursos entre os anos de 2012- - BARBOSA, Gabriella Sousa da Silva (2018)
Violence against women is now understood as a serious violation of human rights. In Brazil, in spite of the international human rights treaties that already incorporated this conception into the legal system, there was only a paradigmatic change in the withdrawal of domestic and family crimes against women within the jurisdiction of special criminal courts as of the enactment of Law nº 11.340 / 2006, Maria da Penha’s Law. Considered as the instrument most accessed by women protected by this law throughout the national territory, the Emergency Protection Measures, provided for between articles 18 to 24 of the norm, are still little explored by the doctrine and jurisprudence of the country, and there is no definition of its legal nature and ignorance of the scope of the exemplary role brought by the legislator. Thus, the present research aimed to evaluate the effectiveness of the judicial provision of the Judiciary Power of Maranhão in the Emergency Prevention Measures trial. For this propose, were used as methodological procedures the bibliographic analysis, documentary analysis, content analysis of the judgments of the Court of Justice of Maranhão, focus groups with members of the Judiciary Power and delegates, in-depth interviews and free and participant observation. As a result, the ineffectiveness of the state jurisdictional provision for guaranteeing women's rights was perceived, especially due to lack of knowledge of the norm, lack of transdisciplinary knowledge and gender, as well as material errors of the courts.